Contemporary quality challenges facing agricultural law in the context of globalisation on the example of the Cuban legal system - Balber Pérez, Miguel Antonio; McCormack Bequer, Maritza de la Caridad (Przegląd Prawa Rolnego, 2018)
Protecting the indigenous food sector through a quality system developed for agri-food products is one of the forms in which Cuban agriculture is striving in its attempts to oppose the effects of globalisation. Consequently, the current agricultural policy implemented in Cuba aims at increasing the professionalism in the food sector, among others, through the introduction of cyclical training of agricultural workers in the field of manufacturing technologies developed for agriculture and by improving their professional qualifications, as well as by an on-going programme of improving the state system of certification of agri-food products, raising the quality standards of accredited laboratories set up for testing food quality, as well as improving the work system certification, especially in the field of the application of risk analysis techniques and the control of points that are critical to food production. There are numerous sanctions provided for in the Cuban system for failure to implement the recommended agricultural policy and the legislation implementing it. They are contained in Decree No. 182 of 23 February 1998: “On the Standardisation and Quality” and Decree No 267 of 3 September 1999: “Infringement o f the established rules concerning standardisation and quality.” The author believes that the adopted regulation on the protection of the quality of agri-food products has contributed to the increase in the attractiveness of the Cuban agricultural sector and has also contributed to ensuring an adequate level of food quality and safety.